OKPROPERTI.COM BUSINESS STRATEGY FOR VILLA SALES IN BALI DURING THE COVID-19 PANDEMIC - Sasrawan Mananda, IGPB.; Mahendra, Ida Bagus Made; Darsana, I Wayan (Jurnal IPTA (Industri Perjalanan Wisata); Vol 9 No 2 (2021): Jurnal IPTA (December 2021), 2021)
The Covid-19 pandemic has changed people's habits in carrying out their activities, including in fulfilling their needs from offline to online, even though economic activity had decreased, but the opportunity to earn income is still open, including buying and selling property villas in Bali through an online platform. One of the platforms that are newly formed one is okproperti.com. During the pandemic period around 4 million people in Indonesia every month are looking for property in Bali and two out of three people want to buy property within the next year and for almost two consecutive quarters this year, said the villa price index continued to decline. The demand for property listings continues to tend to increase, even though at the time of the lockdown it was decreasing, but in August 2020 there was an increase, which was a sign that interest in property was starting to rise. The increase in villa sales was driven by various factors, apart from lower prices; the government also provided a 100% discount on value added tax borne by the government for home purchases. Apart from that, Indonesia Bank's policy interest rate is currently at the level of 3.5%. Okproperti.com as a property sales information provider platform has a strategy that is to continue to align what consumers need. Based on search trends on okproperti.com, the most sought-after villas are homes priced below 2 billion Rupiah with complete facilities. Okproperti.com as a property technology company, answers the needs of consumers who are looking for information online, not only presenting villa listings but also a one stop solution including legality, mortgages so that villa seekers get their dream home.